2020
DOI: 10.3390/su12041449
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Evaluation of Renewable and Nuclear Energy among Higher Education Students

Abstract: Renewable and nuclear power technologies are considered alternatives to fossil-based power. However, which of the two is superior remains a matter of contention. Besides technological development, local access to resources, and energy policies, social acceptance is a key issue; informing future decisions on energy sources thus requires a complex approach. Personal attitudes to energy technologies may differ from professional opinions and national policies. The purpose of this study is to explore the attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Moreover, the system structure of the distribution may affect usability and acceptance [18]. Relevant literature confirms the authors' opinion [14] [19] [20] [20] [22] that an extensive multicriteria evaluation must be applied for exploring the factors of acceptance by considering the local issues [23].…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, the system structure of the distribution may affect usability and acceptance [18]. Relevant literature confirms the authors' opinion [14] [19] [20] [20] [22] that an extensive multicriteria evaluation must be applied for exploring the factors of acceptance by considering the local issues [23].…”
Section: Introductionmentioning
confidence: 94%
“…Thus, AHP is a powerful tool for comparison and ranking intangible criteria and solutions [16]. Many manuscripts have posed questions regarding the possible support of AHP related to sustainable development topics [17], and many other pairwise comparison approaches are available that are related to sustainability issues [18,19]. As highlighted by [20], AHP can be combined with almost all the well-known MCDM methods.…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…How will higher education levels affect the adoption of renewable energy and nuclear power? Based on the research of 250 randomly selected Hungarian higher education students, Berényi et al [ 70 ] showed that solar energy is appreciated, but confidence in nuclear power is low, except for its future role. These results suggest that general knowledge and education level can perform different functions for different energy sources.…”
Section: Theoretical Background Research Model and Hypothesesmentioning
confidence: 99%